Multiphoton fluorescence excitation: new spectral windows for biological nonlinear microscopy. - Xu, C (1996)
Intrinsic, three-dimensionally resolved, microscopic imaging of dynamical structures and biochemical processes in living preparations has been realized by nonlinear laser scanning fluorescence microscopy. The search for useful two-photon and three-photon excitation spectra, motivated by the emergence of nonlinear microscopy as a powerful biophysical instrument, has now discovered a virtual artist's palette of chemical indicators, fluorescent markers, and native biological fluorophores, including NADH, flavins, and green fluorescent proteins, that are applicable to living biological preparations. More than 25 two-photon excitation spectra of ultraviolet and visible absorbing molecules reveal useful cross sections, some conveniently blue-shifted, for near-infrared absorption. Measurements of three-photon fluorophore excitation spectra now define alternative windows at relatively benign wavelengths to excite deeper ultraviolet fluorophores. The inherent optical sectioning capability of nonlinear excitation provides three-dimensional resolution for imaging and avoids out-of-focus background and photodamage. Here, the measured nonlinear excitation spectra and their photophysical characteristics that empower nonlinear laser microscopy for biological imaging are described.